Distress and satisfaction with research participation: Impact on retention in longitudinal disaster research. (March 2018) - Gibbs, Lisa; Molyneaux, Robyn; Whiteley, Sonia; Block, Karen; Harms, Louise; Bryant, Richard A.; Forbes, David; Gallagher, H. Colin; MacDougall, Colin; Ireton, Greg
Abstract: Previous studies of the impact of post-trauma research participation indicate that while the research experience may be emotional, it can still be valued by participants. This paper describes participant experiences of the Australian post-bushfire research study–Beyond Bushfires. It examines the relationships between distress during research participation, probable mental health conditions, and satisfaction with the research experience over time. A range of strategies was incorporated into the study, including a distress and risk assessment and referral protocol, to minimise any risk of harm for people who had experienced the 2009 bushfires and their aftermath. Participants included 1056 respondents (Wave 1) interviewed via telephone and web-based survey between December 2011 through January 2013, and 736 (76.1%) of the participants were re-surveyed between July and November 2014 (Wave 2). Research impact was monitored through two questions about survey experience on each occasion. Reported distress at completing the survey was generally low, while overall satisfaction was relatively high. Participants' reported satisfaction was not associated with their reported level of distress as a result of the survey; and reported participation distress at Wave 1 did not predict whether a respondent would return to complete the survey at Wave 2. Fire-related Posttraumatic stress symptoms were associated with increased satisfaction and likelihood to return at Wave 2. These findings suggest that for Beyond Bushfires survey respondents the perceived benefits outweighed the costs of participation over time.